Tra subalternità e autonomia. Tracce di Gramsci nel “pensiero africano” e nella ricerca africanista - Ciavolella, Riccardo (International Gramsci Journal, 2023)
This is the Abstract of the Italian-language article by Riccardo Ciavolella on the relevance, and difficulties, of translating Gramscian concepts in the contexts of sub-Saharan Africa.